Strategy transformation of information fusion method in smart home environment (Universitas Pendidikan Indonesia (UPI), 2024)
The rapid advancement of information technology has revolutionized various aspects of life, including education. The emergence of information fusion technology, which integrates multiple data sources and sensors, presents new opportunities to enhance learning effectiveness. Smart homes, with their integration of advanced technologies, provide an ideal context to implement information fusion method strategies in education. This research aims to explore and analyze the transformation of information fusion method strategies in smart home environments. Identifying and formulating effective information fusion method strategies for online learning in smart home environments. Employing a qualitative approach, the research delves into the in-depth exploration and contextual understanding of information fusion method strategy transformation in smart home environments. Data is collected through various methods, including observation, interviews, and document analysis. The research findings provide valuable insights into the design and implementation of information fusion method strategies in smart home environments. These findings contribute to the development of innovative and student-centered learning strategies in the era of smart homes.